2010
DOI: 10.1590/s2176-94512010000500017
|View full text |Cite
|
Sign up to set email alerts
|

Reprodutibilidade das mensurações da espessura das tábuas ósseas na tomografia computadorizada Cone-Beam utilizando diferentes protocolos de aquisição de imagem

Abstract: INTRODUÇÃO: quanto menor a dimensão do voxel, maior a nitidez da imagem de tomografia computadorizada Cone-Beam (TCCB), porém, maior a dose de radiação emitida. OBJETIVOS: avaliar e comparar a reprodutibilidade da mensuração da espessura das tábuas ósseas vestibular e lingual em imagens de TCCB, utilizando diferentes protocolos de aquisição de imagem com variação da dimensão do voxel. MÉTODOS: exames de TCCB foram tomados de 12 mandíbulas humanas secas, com dimensão do voxel de 0,2; 0,3 e 0,4mm, no aparelho i-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 18 publications
0
2
0
2
Order By: Relevance
“…Some limitations in accuracy have been reported for 0.3-mm voxel CBCT image evaluations, although they allow for precise measurements. [27][28][29] Alveolar bone with a thickness less than 0.3 mm may wrongly be diagnosed as ABD 28 and still be overestimated in a false-positive result in very thin bony plate regions. 28 Peterson et al 30 also reported an increase in the prevalence of ABD when measured using CBCTs as compared with clinical measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Some limitations in accuracy have been reported for 0.3-mm voxel CBCT image evaluations, although they allow for precise measurements. [27][28][29] Alveolar bone with a thickness less than 0.3 mm may wrongly be diagnosed as ABD 28 and still be overestimated in a false-positive result in very thin bony plate regions. 28 Peterson et al 30 also reported an increase in the prevalence of ABD when measured using CBCTs as compared with clinical measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The thickness of the anterior alveolar bone has been investigated using CBCT (Chen et al, 2010;Menezes et al, 2010;Nowzari et al, 2012), yet few studies have assessed the height and inclination of alveolar bone, which might be the result of difficulty in selecting reference lines on 2D sections that generated from 3D CBCT scans. The lower mandibular line (LML) defined as the bisecting line of the right and left tangent lines to the lower border of mandibular angles and the mandibular symphysis (Downs, 1948;Yamada et al, 2007), and another line passing through the point menton and tangent to the most superior point in inferior border of the mandibular body (Yu et al, 2009), have been used to assess the inclination of the lower incisors and the overlying alveolar bone.…”
Section: Introductionmentioning
confidence: 99%
“…A tomografia computadorizada por feixe cônico foi à ferramenta utilizada para realização desta pesquisa. Este exame permite avaliar as tábuas ósseas com nitidez expondo o paciente a menor dose de radiação que um exame obtido por tomografia multislice (Kobayashi et al, 2004;Loubele et al, 2008 Fuhrman, 1996;Tsunori et al, 1998;Nakajima et al, 2005;Mol;Balasundaram, 2008;Loubele et al, 2008;Garib et al, 2010;Lund et al, 2010;Menezes et al, 2010). Os softwares disponíveis para avaliar imagens geradas por tomografias computadorizadas oferecem ferramentas que permitem ajuste de brilho, contraste e ampliação das imagens visando o aumento de nitidez das mesmas (Fuhrman, 1996;Tsunori et al, 1998;Kobayashi et al, 2004;Loubele et al, 2008;Mol;Balasundaram, 2008;Lund et al, 2010).…”
Section: 2)unclassified
“…Testes realizados porMenezes et al(2010) encontraram precisão em medidas de espessura alveolar nos protocolos de aquisição da imagem com voxel…”
unclassified